Psychological Challenges in Gymnasts Before Porprov East Java IX: Depression, Anxiety, Stress, and Emotional Eating - Yuhantini, Eva Ferdita; Priambodo, Anung (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This This study aims to examine the psychological challenges experienced by gymnasts in Gresik City who are preparing to participate in the 9th East Java Porprov competition, with a special focus on anxiety, depression, stress, and their relationship to emotional eating behavior. The sample consisted of 15 gymnasts, including 2 male gymnasts and 13 female gymnasts, recruited from the Gresik City Gymnastics Training Center. Data were collected using the Depression Anxiety Stress Scale (DASS-42) and the Dutch Eating Behavior Questionnaire (DEBQ). The statistical test used in this study was the Shapirow-Wilk test to determine the normality of the data. The Pearson correlation test was used to determine the relationship between depression, anxiety and stress with emotional eating. The results of this study indicate that there is a relationship between anxiety and stress in gymnasts. This may be due to the psychological burden experienced by athletes during the run-up to the competition. However, the results of the relationship between emotional eating and anxiety and stress did not show a significant relationship. These results indicate that emotional eating is not an intervention carried out by gymnasts when they experience anxiety and stress. This study concludes that it is very important to use appropriate interventions when athletes experience psychological stress. Athletes really need a support system that can provide them with mental well-being. Further research is expected to explore more about the long-term impacts and the use of larger and more diverse samples